ANTIOXIDANT AND ANTI-INFLAMMATORY POTENTIAL OF QUCERTIN - B., Muthukala; K., Sivakumari; K., Ashok (International Journal of Current Pharmaceutical Research, 2015)
Objective: In the present study the antioxidant potential and anti-inflammatory effect of qucertin compound was assessed. Methods: The antioxidant potential of the drug was determined by ORAC assay and DPPH assay. Likewise for anti-inflammatory studies, RBC's were collected from healthy volunteers and the hemo protective activity of the drug was carried out at various concentrations. Results: The results showed that qucertin has a positive effect on both the parameters. The probable reasons governing the facts are discussed in the light of previous literature. Conclusion: The results show that qucertin seems to be a good replacement for chemical therapeutic drugs as it has antioxidative and anti-inflammatory properties.